Statics of Historic Masonry Constructions - Como, Mario (Springer Series in Solid and Structural Mechanics,, 2016)
This successful book, which is now appearing in its second edition, presents a comprehensive new Statics of Masonry Constructions. Masonry constructions are the great majority of the buildings in Europe's historic centres and the most important monuments in its architectural heritage. Given the age of these constructions, the demand for safety assessments and restoration projects is pressing and constant. The book you hold in hands contributes to fill this demand. The second edition integrates the original text of the first edition with new developments, widening and revisions, due to recent research studies achievements. The result is a book that gives a complete picture of the behaviour of the Masonry Constructions. First of all, it gives the fundamentals of its Statics, based on the no-tension assumption, and then it develops the Limit Analysis for the Masonry Constructions. In this framework, through an interdisciplinary approach combining Engineering and Architecture, the book also investigates the static behaviour of many historic monuments, such as the Pantheon, the Colosseum, the domes of Santa Maria del Fiore in Florence and St Peter's in Rome, as well as the Leaning Tower of Pisa, the Gothic Cathedrals. Finally, the book gives an in-depth study of  masonry buildings under seismic actions.